Standardization of Human Calcific Aortic Valve Disease in vitro Modeling Reveals Passage-Dependent Calcification - Goto, Shinji; Rogers, Maximillian A.; Blaser, Mark C.; Higashi, Hideyuki; Lee, Lang H.; Schlotter, Florian; Body, Simon C.; Aikawa, Masanori; Singh, Sasha A.; Aikawa, Elena (Frontiers in Cardiovascular Medicine, 2019)
Aortic valvular interstitial cells (VICs) isolated from patients undergoing valve replacement are commonly used as in vitro models of calcific aortic valve disease (CAVD). Standardization of VIC calcification, however, has not been implemented, which impairs comparison of results from different studies. We hypothesized that different culture methods impact the calcification phenotype of human VICs. We sought to identify the key parameters impacting calcification in primary human VICs to standardize CAVD in vitro research. Here we report that in calcification media containing organic phosphate, termed osteogenic media (OM), primary human VICs exhibited a passage-dependent decrease in calcification potential, which was not observed in calcification media containing inorganic phosphate, termed pro-calcifying media (PM). We used Alizarin red staining to compare the calcification potential of VICs cultured in OM and PM between the first and fourth passages after cell isolation from human CAVD tissues. Human VICs showed consistent Alizarin red stain when cultured with PM in a passage-independent manner. VICs cultured in OM did not exhibit consistent calcification potential between donors in early passages and consistently lacked positive Alizarin red stain in late passages. We performed whole cell, cytoplasmic and nuclear fractionation proteomics to identify factors regulating VIC passage-dependent calcification in OM. Proteomics cluster analysis identified tissue non-specific alkaline phosphatase (TNAP) as a regulator of passage-dependent calcification in OM. We verified an association of TNAP activity with calcification potential in VICs cultured in OM, but not in PM in which VICs calcified independent of TNAP activity. This study demonstrates that media culture conditions and cell passage impact the calcification potential of primary human VICs and should be taken into consideration in cell culture models of CAVD. Our results help standardize CAVD modeling as part of a greater effort to identify disease driving mechanisms and therapeutics for this unmet medical need.